XV International Conference on Durability of Building Materials and Components. eBook of Proceedings 2020
DOI: 10.23967/dbmc.2020.129
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Sulfate Attack Resistance of Reactive Powder Concrete

Abstract: This paper is the study of sulfate attack resistance of reactive powder concrete (RPC). RPC that is also known as ultra-high performance concrete is a special type of concrete material obtained when fine powders like silica fume (SF) are added into the concrete mortar along with very low waterto-binder ratio (w/b). SF is a pozzolanic material obtained as a by-product of silicon metal or ferrosilicon alloys production. In this study, total 6 different RPC mixtures with various w/b (0.18, 0.22 and 0.26) and vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Bektimirova et al [16] showed that reactive powder concrete exhibits good sulphate resistance by analyzing the different mixtures of reactive powder concrete attacked with different sodium sulphate concentrations. Rasheed et al [17] stated that the use of the polymer in reinforced concrete subjected to sulphate salt attack is not advisable.…”
Section: Introductionmentioning
confidence: 99%
“…Bektimirova et al [16] showed that reactive powder concrete exhibits good sulphate resistance by analyzing the different mixtures of reactive powder concrete attacked with different sodium sulphate concentrations. Rasheed et al [17] stated that the use of the polymer in reinforced concrete subjected to sulphate salt attack is not advisable.…”
Section: Introductionmentioning
confidence: 99%